Diagnosis of Pentatrichomonas hominis from domestic cats in Southeastern Brazil - dos Santos, Caroline S.; McIntosh, Douglas; Berto, Bruno P.; de Jesus, Vera Lúcia T.; da Rocha, Cristiane N.C.; Fernandes, Júlio I.; Scott, Fábio B.; Lopes, Carlos Wilson G. (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. dos Santos C.S., McIntosh D., Berto B.P., de Jesus V.L.T., da Rocha C.N.C., Fernandes J.I., Scott F.B. & Lopes C.W.G. Diagnosis of Pentatrichomonas hominis from domestic cats in Southeastern Brazil. [Diagnóstico de Pentatrichomonas hominis em gatos no sudeste do Brasil.] Revista Brasileira de Medicina Veterinária, 37(Supl.1):25-31, 2015. Curso de Pós-Graduação em Ci- ências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR-465 Km 7, Campus Seropédica, RJ 23897-970, Brasil. E-mail: carolinespitz@yahoo.com.br The parabasalid flagellate Tritrichomonas foetus is recognized as the causative agent of large bowel diarrhea in domestic cats. A second species of parabasalid flagellate Pentatrichomonas hominis, has also been reported in association with domestic cats, albeit almost exclusively as a commensal organism. However, there is growing evidence to suggest that P. hominis may also be involved in feline gastro-intestinal disorders including diarrhea and that the incidence of infection with P. hominis may have been underestimated due to it being misidentified as T. foetus. The aim of the current study was to establish the basis for routine morphological identification of P. hominis employing light microscopy and to apply the methodology to the examination of cases of diarrhea in a laboratory population of Brazilian domestic cats (n =39). A detailed morphological description of P. hominis isolated from 11 cats with diarrhea was produced and molecular analyses were performed in support of the morphological data and to demonstrate the absence of T. foetus in infected cats. All animals with diarrhea were demonstrated to be infected solely with P. hominis. The findings of the current study provide a straight forward and validated method for the differential diagnosis of P. hominis and contribute to the on-going debate surrounding the pathogenic potential of this parabasalid flagellate.